A new remote monitoring device to track magnetic resonance imaging machine cooling system failures - Oussama Elallam; Mohamed Hamlich (Institute of Advanced Engineering and Science, 2022)
The magnetic resonance imaging (MRI) machine cooling system has a vital role in the conduct of MRI examinations because a shutdown of the MRI cooling system in the absence of the manipulators can lead to grave consequences over time, like quench, which is the vaporization of helium liquid in the MRI tank, and it's the most expensive MRI failure. To limit the risks of this problem, several companies have tried to develop a monitoring system to track MRI cooling system failures but all solutions proposed are complicated and demand many connections with MRI. The proposed solution is simple, easy, and efficient requires only one joint with the helium compressor, and it has a humidity and temperature sensor to detect quench incident, it works using an advanced monitoring algorithm that evaluates the status of the cooling system and identifies breakdowns, in case of failure our system will send short message service (SMS) notifications and emails to the customer service team. The proposed solution shows the potential for starting the research to understand the relationship between the behavior of the MRI cooling system and the quench using machine learning algorithms.